2007
DOI: 10.1136/ip.2006.012468
|View full text |Cite
|
Sign up to set email alerts
|

Geomatics in injury prevention: the science, the potential and the limitations: Figure 1

Abstract: By supporting novel approaches to injury prevention, geomatics has a great potential for efforts to combat the burden of injury. Despite some limitations, those with an interest in injury prevention could benefit from this science.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…The use of GIS as a tool to link social, economic, ecologic, and demographic factors is critical for better understanding of injury and its prevention. 22 The ability to map the distribution of injury and populations at risk as well as spatially analyzing these data can assist in the planning and targeting of interventions. 23 Indeed, the mapping of the factors deemed to be important to health and media experts for an AHT prevention campaign was used to target the campaign in areas of the city and populations in greatest need of the message.…”
Section: Discussionmentioning
confidence: 99%
“…The use of GIS as a tool to link social, economic, ecologic, and demographic factors is critical for better understanding of injury and its prevention. 22 The ability to map the distribution of injury and populations at risk as well as spatially analyzing these data can assist in the planning and targeting of interventions. 23 Indeed, the mapping of the factors deemed to be important to health and media experts for an AHT prevention campaign was used to target the campaign in areas of the city and populations in greatest need of the message.…”
Section: Discussionmentioning
confidence: 99%
“…Most revolve around injury prevention issues such as finding clusters of injuries for potential mitigation interventions such as traffic quieting and education of populations at risk. 15,[17][18][19][20][21][22] There have been two studies of the clustering of cardiac arrest cases that showed differential location effects of the application of bystander cardiopulmonary resuscitation (CPR) 23 and the response of non-first-due fire apparatus 24 on survival rates. A few studies have evaluated resource deployment strategies, usually helicopters for trauma incidents.…”
Section: Discussionmentioning
confidence: 99%
“…In ArcGIS, the latter calculates the density of points within an investigated geospatial radius, weighing the values according to the attributes of the point and allocating them to each output raster cell [45]. This method is useful primarily as a visualization technique [46] (p. 53). The choice was made paying particular attention to the extension of the artificial surfaces, as polygons had distinct areas within the established radius.…”
Section: Spatial Analysismentioning
confidence: 99%